Fatty Acid Methyl Esters Production from Waste Catfish Fat (Pangasius Hypothalamus) Using Barnacle-Zno As A Catalyst - Norhafiza Mohd Khazaai, Siti; Farah Wahida Abdul Wahid Baki, Nur; Pragas Maniam, Gaanty; Hasbi Ab. Rahim, Mohd (International Journal of Engineering and Technology, 2018)
The abundance and diverse populations of Barnacle shells catching the intention as a source of calcium oxide catalyst to transesterify waste catfish fat into methyl ester. Calcium oxide supported with zinc oxide was prepared by ball milling method at 1:2 ratios, calcined for 3 h at 400 Â°C. The characterization of catalyst revealed both metals were well integrated into a bimetallic oxide. The optimal conditions were found to be: methanol/oil mass ratio, 10:1; catalyst amount, 11 wt% at the reaction temperature, 65 Â°C with 3 h of reaction time achieving 85.7% of methyl ester conversion. Both feedstock and catalyst from waste source have been successfully utilized to produce biodiesel.Â Â